Cognitive load on working memory both encourages and discourages reasoning bias regarding the mental states of others. (4th April 2013) - Maehara, Yukio; Saito, Satoru
Abstract: Theory of mind (ToM) refers to the ability to reason about the mental states of others. An increasing number of studies have revealed that working memory (WM) plays an important role in ToM. The present study applied WM loads to adults during a ToM task in order to investigate the impact on mental‐state reasoning performance. The task required participants to estimate the probabilities of several possible behaviours for a protagonist following the presentation of a ToM story. Participants were also required to maintain a meaningless two‐ (light WM load) or seven‐letter English alphabet string (heavy WM load) during story comprehension and mental‐state reasoning. The results show that the combination of light WM load applied during story comprehension with heavy WM load during mental‐state reasoning results in an overestimation of the probability that the protagonist's behaviour will accord with a participant's knowledge. Conversely, a heavy WM load applied during story comprehension, regardless of the type of WM load during mental‐state reasoning, did not result in this probability estimation bias. We discuss these findings from the perspective of a WM representation account.